For the right side its 12.5
Answer:
D
Step-by-step explanation:
because if you add the numbers up you will get the answer easy :)
Answer: Choice D. y = (x-1)^2 - 3
The vertex is (h,k) = (1,-3). So h = 1 and k = -3.
We have a = 1 as the leading coefficient.
Plug those values into the equation below
y = a(x-h)^2 + k
y = 1(x - 1)^2 + (-3)
y = (x - 1)^2 - 3
X^2 + y^2 - 2x + 8y - 47 = 0
x^2 + y^2 - 2x + 8y = 47
(x^2 - 2x) + (y^2 + 8y) = 47
(x^2 - 2(1)x) + (y^2 + 2(4)y) = 47
(x^2 - 2(1)x + 1^2) + (y^2 + 2(4)y + 4^2) = 47 + 1^2 + 4^2
(x - 1)^2 + (y + 4)^2 = 64 = 8^2
r=8
Answer:
63 cause there equal
Step-by-step explanation: